Pengaruh Penggunaan Rekam Medis Elektronik (Rme) Dan Stres Kerja Terhadap Turnover Intention (TI) Tenaga Perawat Dengan Kepuasan Kerja Sebagai Variabel Mediasi - Simon, Flyndie; Widjaja, Bernard Tirto; Gunardi, Wani Devita (LPPM Universitas Respati Indonesia, 2025)
Turnover intention is an enemy within an organization and difficult to be detected early. In 2019, the turnover rate for nurses reached its highest value compared to the previous four years. The era of digital transformation has the potential to provide opportunities for improving work processes, including in the healthcare world such as the form of electronic medical record systems. This study is a quantitative, cross-sectional study using a questionnaire distributed to 80 emergency department nurses in West Jakarta. Data was analyzed using SEM partial least squares (PLS) method. The results showed that the use of electronic medical records (EMR) and work stress had a significant effect on job satisfaction, work stress and job satisfaction had a significant effect on turnover intention, and the effect of work stress on turnover intention can also be mediated by job satisfaction. On the other hand, the use of EMR did not have a significant effect on turnover intention and the effect of EMR usage on turnover intention could not be mediated by job satisfaction. From this study, the effectiveness of implementing the EMR system in healthcare services can be examined in relation to work stress, job satisfaction, and turnover intention of working healthcare professionals, especially nurses in the emergency department.